THE NEED AND POSSIBILITY OF USING PEDAGOGICAL TECHNOLOGIES IN MODERN HIGHER EDUCATION (EDUCATION IN THE 21ST CENTURY, 2025)
The article, from the point of view of system analysis of the issue, provides a description of the main modern pedagogical technologies used in higher educational institutions of Armenia, highlights the features, principles, forms, methods and means of educational activities.Today, ineffective forms and methods of teaching are eliminated, they are replaced by more advanced, newly developing ideas that should be introduced gradually, in conditions of effectiveness confirmed by pedagogical scientific experience, naturally, eliminating gaps in existing pedagogical theories.Recognizing that the division of innovative and traditional technologies is very conditional, it is proposed not to contrast them, but to complement them.Innovative technology differs from traditional technology only in that it is more focused on the needs of modern society, on the student's own personality, requiring from him the desire for self-development and self-improvement, the ability to apply the knowledge gained during study knowledge in practice.At the same time, the necessity of rethinking a number of fundamental concepts is substantiated.The task considered in the article is to identify the necessity and possibility of using pedagogical technologies in modern higher education.The importance of didactics, teaching methods and pedagogical technologies in the activities of modern higher education is discussed.New state approaches to education are based on a competence-based approach, which allows the subordination of knowledge to the achievement of educational goals, emphasizing the practical focus, preparing graduates for practical activities and actions.Particular attention is paid to the practical focus, preparing graduates for practical activities and actions.
Keywords: higher education; strategy; concept; innovation; pedagogical technology; independent learning; teacher; student